Influence of partial suckling of crossbred dairy cows on milk offtake and calf growth in the Ethiopian highlands - Little, D.A.; Anderson, F.M.; Durkin, J.W. (Springer, 1991)
Investigates the potential benefits of restricted suckling of crossbred cows in the Ethiopian highlands with special emphasis on maximising the efficiency of resoruce utilisation. Examines nutrient concentrations in grass hay fed and refused, and productivity characteristics of crossbred cows and their calves subjected either to a partial suckling regime or one of bucket in the Ethiopian highlands.